Pop perspectives : - Gray-Rosendale, Laura (McGraw-Hill, 2008)
Pop Perspectives provides students with a solid intellectual foundation in critical thinking, reading, writing, and classical argument through up-to-date, popular culture models, exercises, and assignments that are immediately relatable to the student's world.